Tax planning implementation on income tax article 21 of permanent employees for efficient payment of tax burden at PT. SC - Lestari, Nur Ayu; Siringoringo, Whereson (JAAF (Journal of Applied Accounting and Finance), 2024)
This research aims to understand the application of tax planning for Income Tax Article 21 at PT. SC and to determine the effect of applying each method used in the implementation of tax planning for Income Tax Article 21 related to the efficiency of paying the company's tax expense. This research uses a qualitative descriptive research method. Data sources were obtained through interviews and documentation. The results obtained through this research show that the policy of PT. SC in the application of Gross Up is implemented to reduce the expense on corporate income tax and so that employees are motivated to increase their productivity without worrying about the taxes that must be paid. However, tax planning for Income Tax Article 21 implemented by PT. SC is not yet efficient regarding the taxes that must be paid because the application of the Gross Up calculation causes the payment of the tax expense during one financial year to be greater than with other methods.